Improved hole injection in organic light emitting devices by gold nanoparticles. Issue 1 (1st December 2014) - Jesuraj, P. Justin; Jeganathan, K.
Abstract : AuNPs at various surface coverage. Abstract : We report the role of surface coverage of gold nanoparticles (AuNPs) at the interface of anode/hole transport layer (HTL) in organic light emitting devices (OLEDs). AuNPs with an optimized coverage of 2.10% at the ITO/α-NPD interface increase the hole injection into the HTL which results in three orders of magnitude enhancement in the current density in OLEDs. At low surface coverage, injected holes are trapped at the interface. The zero field mobility resulting from the Poole–Frenkel equation is responsible for the improved hole injection into the HTL layer. The turn-on voltage of OLEDs was efficaciously lowered to 3 V with substantial increment in luminescence. The local field generated by AuNPs under electrical biasing with sufficient coverage is ascribed to the improved characteristics in OLEDs.